Menangkal hoax melalui workshop literasi media dan bedah film “Tilik” bagi Karang Taruna Desa Karyamekar - Chotijah Fanaqi; Arti Nurdianti Chairunnisa (Yumary: Jurnal Pengabdian kepada Masyarakat, 2020)
Purpose: The aim of the media literacy workshop through the review of the Tilik film is to build awareness and understanding for Karyamekar associations in an effort to ward off hoaxes that are rife on social media. The discussion and review of this film was in the context of the implementation of Community Service which was held by the Garut University Service Team in collaboration with the Youth Organization of Karyamekar Village, Cilawu District, Garut Regency. Method: The method used is a workshop and film surgery "TILIK". Results: The results of these activities indicated that the workshop with the discussion method and providing examples of the latest cases (film review) was quite effective. This can be seen in the enthusiasm of the participants, as well as the ongoing discussion process. Conclusion: The Tilik Film Review activity has a very positive impact on the participants to foster their interest in media literacy. Keywords: Media literacy, Hoax